Characterization of antibody responses to SARS‐CoV‐2 in convalescent COVID‐19 patients. Issue 4 (10th November 2020) - Liu, Chuanmiao; Yu, Xiaoqi; Gao, Chunming; Zhang, Li; Zhai, Hui; Hu, Yanan; Liu, Enhui; Wang, Qiong; Gao, Yu; Wei, Dong; Zhang, Donghua; Han, Yue; et al.
Abstract: The coronavirus disease 2019 (COVID‐19) is a pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). However, little is known about the durability of the antibody response during COVID‐19 convalescent phase. We investigated the prevalence of anti‐SARS‐CoV‐2 specific antibodies including immunoglobulin G (IgG) and immunoglobulin M (IgM) antibodies and the dynamic changes in antibody levels in convalescent COVID‐19 patients. A total of 159 blood samples were collected from 52 recovered COVID‐19 patients up to six months after symptom onset for longitudinal serological tests. The positive rate of IgG and IgM antibodies was 92.3% and 90.4% in the first month after symptom onset, and the seropositivity of IgG antibody remained high at all follow‐up time points, whereas the seropositivity of IgM antibody decreased to 22.73% by the sixth months after symptom onset. The level of IgG antibody was stable, the level of IgM antibody decreased slightly in the early convalescent phase and was detected in only five patients in the sixth month after symptom onset. The level of IgG antibody was higher in the severe and critical group than in the moderate group. The anti‐SARS‐CoV‐2 specific antibodies have a long‐term persistence in convalescent COVID‐19 patients, whether they have long‐term protection need to be further investigated.